ETIKA BELAJAR SISWA PERSPEKTIF SYAIKH MUHAMMAD SYAKIR DALAM KITAB WAṢĀYĀ AL-ᾹBĀ’ LIL ABNĀ’ DAN RELEVANSINYA DENGAN KONTEKS KEKINIAN - Saputra, Andi (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2024)
This thesis discusses the ethics of student learning according to Syaikh Muhammad Syakir in the book Waṣāyā al-Ᾱbā’ Lil Abnā and its Relevance in the Current Context. Habituation of learning ethics is very important for students to be familiar with the ethics of learning to gain knowledge that is blessing and beneficial. This study aims to explain the ethics of student learning according to Syaikh Muhammad Syakir described in Waṣāyā al-Ᾱbā’ Lil Abnā and its relevance in the current context. Research method used is qualitative with a character study approach. The result of the research is to divide student learning ethics into four parts: self-study ethics, learning ethics towards lessons, learning ethics towards teachers, and learning ethics towards friends. The four divisions are still relevant and need to be applied in the current context. In addition, student learning ethics also involve the use of technology wisely and responsibly, including utilizing accurate learning resources while maintaining their integrity. So, it is important for students to learn and apply learning ethics in their daily lives.